Spiritual Intelligence and School Well Being Associated With Lower Work Stress: Kecerdasan Spiritual dan Kesejahteraan Sekolah Berkaitan dengan Tingkat Stres Kerja yang Lebih Rendah - Isrofi Sukmania; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Students who simultaneously engage in academic study and employment frequently experience work stress arising from role conflict, academic demands, and occupational responsibilities, potentially disrupting academic performance and daily functioning. Specific Background: Internal psychological resources such as spiritual intelligence and external environmental conditions including school well-being are recognized as factors related to students’ stress experiences within academic and occupational contexts. Knowledge Gap: Empirical studies simultaneously examining spiritual intelligence and school well-being as predictors of work stress among working university students remain limited. Aims: This study examined the relationship between spiritual intelligence and school well-being with work stress among working students at Universitas Muhammadiyah Sidoarjo. Results: Using a quantitative correlational design with purposive sampling, 297 working students were selected from a population of 1,291 students. Data were collected using The Job Stress Scale, The Spiritual Intelligence Self-Report Inventory SISRI-24, and a school well-being scale. Multiple linear regression analysis indicated significant negative relationships between spiritual intelligence and work stress (β = -0.966; p < 0.001) and between school well-being and work stress (β = -0.231; p = 0.043). Simultaneous testing showed statistical significance (F = 491.523; p < 0.001), with both variables explaining 64.8% of work stress variance. Novelty: This study integrates internal spiritual capacity and campus welfare constructs within a single regression framework focusing on working university students. Implications: The findings indicate the importance of fostering students’ spiritual capacities and supportive campus environments as components of stress management strategies within higher education systems. Highlights: Higher Sisri-24 Scores Corresponded With Reduced Occupational Strain Indicators. Campus Welfare Dimensions Including Having, Loving, Being, and Health Showed Significant Statistical Relationships With Psychological Tension. Predictive Modeling Explained 64.8% of Variance Among Employed University Participants. Keywords: Spiritual Intelligence, School Well-Being, Working Students, Work Stress, Multiple Linear Regression